Organic livestock in the Republic of Croatia and Europe : Ekološko stočarstvo u Republici Hrvatskoj i Europi - Antunović, Zvonko (Array, 2020)
The aim of the present study was to analyze the situation in organic livestock farming in Croatia and Europe. In the European countries in the year 2017, around 4.5 million cattle, 5.2 million sheep, 1 million pigs and 50 million poultry were registered in organic farming. The highest share of organically registered domestic animals compared to the total population in Europe and the European Union-28 was in cattle (3.5% and 5.2%) and sheep (3.4% and 5.0%), and the lowest in pigs (0.6% and 0.7%). In Croatia the highest share is in sheep (8.57%) and the lowest in poultry (0.02%) number. The largest increase in recent ten years in the EU has been in the number of poultry (by 103%) and the smallest in the number of pigs (by 47.6%), while the increase was the number of cattle and sheep was around 76% and 74%, respectively. In Croatia organic sheep production increased the most (by 65.0%), while the number of cattle and poultry increased by 62 and 64%, and the smallest increase is in the number of pigs (by 24%). The majority of organic meat of all species of domestic animals is produced in France and in United Kingdom, while organic milk is produced mostly in Germany and France. During the year 2018, most organic beef was produced in the UK and France, organic pork in France and Finland, organic sheep meat in Spain and the UK, organic goat meat in Spain, while most of organic poultry was produced in France and in the UK. A significant increase in the number of livestock in organic farming in Europe and in Croatia indicates an increasing interest in organic livestock farming, not only increase of farmers and processors but also increase of consumers of organic products in European countries.